Character Education Management in Shaping School Culture - Nurul Khasanah; Niswanto Niswanto; Khairuddin Khairuddin (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to obtain an overview of character education management consisting of planning, organizing, implementing, and supervising, as well as evaluating character education programs in shaping school culture at SMAN 1 Banda Aceh. This research uses a qualitative approach with a descriptive type of research. Data collection techniques using observation, interviews, and documentation. The standard of data validity in qualitative research refers to the standards of credibility, transferability, dependability, and confirmability. The data analysis technique used is descriptive qualitative analysis with data reduction, data presentation, and conclusion drawing techniques. The strategy for implementing character education at SMAN 1 is carried out through: integrating values and ethics in subjects, internalizing positive values to all school members, habituation and training, giving examples and examples, creating an atmosphere of character, and civilizing. Evaluation of the character of students can be done using an attitude assessment instrument, or through direct observation. For obstacles in the implementation of character education, namely the lack of parental/environmental attention, the influence of science and technology, and the influence of the covid pandemic for ± 2 years which hampered the character education process. @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;@font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-520082689 -1073697537 9 0 511 0;@font-face font-family:Georgia; panose-1:2 4 5 2 5 4 5 2 3 3; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:647 0 0 0 159 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:IN; mso-fareast-language:IN;.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:11.0pt; mso-ansi-font-size:11.0pt; mso-bidi-font-size:11.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:IN; mso-fareast-language:IN;.MsoPapDefault mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;div.WordSection1 page:WordSection1;